Perancangan Sistem Informasi Inventaris Sarana dan Prasarana Sekolah Berbasis Web - Riski Annisa; Panny Agustia Rahayuningsih; Anna Anna (Fakultas Teknik Universitas Hamzanwadi, 2023)
School is a teaching and learning institution. The problem observed in schools, in general, is that there is still no centrally managed web-based system, one of which is the loss of facility and infrastructure inventory data that is still maintained using Microsoft Excel, or the absence of a unique system to summarize it. Inventory data of facilities and infrastructure in the database or online. If information is needed, the school should look up each one in the office files. As a result of these problems, an application is needed in the form of a site information system and web-based infrastructure, every year the amount of data owned by schools increases and it is difficult to manage it. The manual summary is used to assist service schools in processing data such as information on the inventory of facilities and infrastructure. This research aims to develop an information system capable of managing real estate and infrastructure information in a web-based database system so that the system can connect to the Internet quickly and accurately. The author uses XAMPP as a local hosting server, which includes Apache as an HTTP server, MySQL as a database, Sublime Text 3 as a sentence editor for HTML and PHP scripts, and PHP as a programming language, and uses a browser to view output from web pages, and creates a database with SQL Yog.